Diagnóstico de uma lagoa de infiltração receptora de efluentes tratados de matadouro visando a conservação da bacia hidrográfica do igarapé Água Boa-RR - Martins, Cíntia de Castro Garcia (Universidade Federal de Roraima, 2019)
The great internal and external demand for products of the meat industry triggers an increasing production in that sector and, as a result, wastewater filled with pollutants is generated daily, which can compromise the drainage basin in which it is inserted. In face of that, this research aimed at diagnosing the infiltration pond that receives the treated effluent of the Industrial Slaughterhouse and Cold Storage of Roraima (MAFIR) located in the Água Boa stream’s drainage basin in Boa Vista - RR. A socioeconomic region of small to large size, containing bathing spots and restricted use of water. Looking to preserve the basin, it was monitored with six data collections in dry season from September 2015 to April 2016 in six different sampling points, four of them being on the infiltration pond (LAG) with the treated effluent and two on the Água Boa stream, upstream (IGM) and downstream (IGJ) of LAG, using the following physical, chemical, hidrobiological and microbiological parameters of quality: pH, temperature, total dissolved solids, electrical conductivity, turbidity, salinity, biochemical oxygen demand, total phosphorous, nitrates, nitrites, ammoniacal nitrogen, chlorophyll a, total coliforms, thermotolerant coliforms, Escherichia coli, heterotrophic bacteria and trophic level index. An analysis of the infiltration pond area was also performed using literature review, photographic records and historical satellite images. Based on that, it was verified that the monitored points of the Água Boa stream is an ultraoligotrophic environment, with biological oxygen demand and phosphorous concentrations above the permitted in class 2 waters in April at the IGJ sample point, an unsatisfactory quality for primary contact due to the density of thermotolerant coliforms and E. coli and water quality statistically similar (p<0,05). The treated effluent present at the infiltration pond was homogenous, except for heterotrophic bacteria density, and had concentrations of total dissolved solids, turbidity, total phosphorous, biochemical oxygen demand, chlorophyll a, nitrite and ammoniacal nitrogen, at some point of the monitoring, that could compromise the quality of the Água Boa stream’s superficial water if it became the recipient water body. Another important result is the oscillation of the pond’s superficial area, which currently, corresponds to a 58% increase when compared to 2003 but used to be a 76% increase in 2012, and it’s directly correlated to the amount of slaughtering. Thus, it is concluded that the implementation of the infiltration pond as an alternative recipient for MAFIR’s effluents instead of releasing it directly into the Água Boa stream was really necessary, considering the amount of the treated effluent. However, operational and structural monitoring is required to prevent the contamination of superficial and subterranean water and damage to public health and aquatic life. Lastly, it wasn’t possible to assert that there is a contribution to the degradation of the Água Boa stream’s microbasin caused by the disposal of effluent in the soil done by MAFIR, but it is recommended to implement monitoring actions on the slaughterhouse’s sewage treatment plant, in order to guarantee the microbasin’s conservation.